Pengembangan Model Pembelajaran Kolaboratif Antara Guru dan Orangtua dalam Mendukung Kemajuan Belajar Siswa di Sekolah Dasar Inpres Harekakae - Marsela Luruk Bere; Marianus Teti; Maria Gamyanti Funan (Lembag, 2024)
In the world of education, we really need every support from every circle because a student's success in learning is due to this support. Determine the right model needed to help this progress by determining the right model according to the problems faced by students. In this research, the researcher aims to collaborate between teachers and parents to help the learning progress of elementary school students at SDI Harekakae. The sample I took was 30 students with different abilities so that researchers could measure the extent of collaboration between parents and teachers to help students develop progress. Initial observations in this study provided data from 8 statements, each of which had a weight that did not meet the target of <80% with an average score of 40%. So in this implementation the researcher held a meeting with parents and teachers to enter into a collaboration agreement. In this meeting the teachers agreed to carry out 8 statements by signing the activity contract. During the implementation, researchers carried out monitoring by providing activity observations. However, the results obtained were that 2 statements did not meet the target, while 6 statements met, meaning that out of 8 statements, 80% were successful. So it can be concluded that in collaboration there are several obstacles, in this case family finances also influence.